THE TRADITION OF KHATAM AL-QUR’AN IN ACEH, INDONESIA (AN ETHNOGRAPHIC STUDY IN LAM ILIE TEUNGOH SOCIETY, INDRAPURI-ACEH BESAR) - Muhammad Arifin; Manan, Abdul; Saprijal, Saprijal; Septian Fatianda; Fauzi Ismail (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2024)
The tradition of Khatam al-Qur’an has existed since the era of Prophet Muhammad Saw, in which the Prophet highly recommended his followers to seal (khatam) and read the Qur’an by reciting it from the beginning to the end. This article aims to describe deeply the implementation of the Khatam al-Qu’an in groups and individually, as well as the views of the Khatam al-Qu’an. The instruments used are observation, interview, and documentation. The data were analysed using data reduction, data presentation, and drawing conclusions. The findings show that the tradition of Khatam al-Qur'an is carried out in groups and individually. The Khatam al-Qur'an in the group is only carried out in the holy month of Ramadhan by the village community, either in the mosque or the meunasah. Reciting the Qur’an (tadarus) at the mosque or meunasah during Ramadhan is carried out by men only. They usually complete sealing the Qur'an 1 or 2 times in a Ramadhan month. The implementation of individual Khatam al-Qur'an is carried out on children or teenagers who have completed reading 30 juz of the al-Qur'an. Khatam al-Qur'an done individually does not involve the village community but only his or her friends or other people at the recitation place. The Khatam al-Qur'an is a form of gratitude and glorification of the Qur'an. In addition, it is an embodiment or a sign of victory for an individual or group in studying the reciting of the Qur'an.